Short-term effects of increased CO2, nitrate and temperature on photosynthetic activity in Ulva rigida (Chlorophyta) estimated by different pulse amplitude modulated fluorometers and oxygen evolution. (16th October 2020) - Figueroa, Felix L; Bonomi-Barufi, Jose; Celis-Plá, Paula S M; Nitschke, Udo; Arenas, Francisco; Connan, Solene; Abreu, Maria Helena; Malta, Erik-J; Conde-Álvarez, Rafael; Chow, Fungyi; Mata, Maria Teresa; Meyerhoff, O; et al.
Abstract : Photosynthesis in Ulva rigida, estimated by different methods ex situ and in situ, decreased under changing pH, nitrate and temperature conditions, demonstrating strong interactions between global climate factors. Abstract: Short-term effects of p CO2 (700–380 ppm; High carbon (HC) and Low carbon (LC), respectively) and nitrate content (50–5 µM; High nitrogen (HN) and Low nitrogen (LN), respectively on photosynthesis were investigated in Ulva rigida (Chlorophyta) under solar radiation ( in-situ ) and in the laboratory under artificial light ( ex-situ ). After six days of incubation at ambient temperature (AT), algae were subjected to a 4 °C temperature increase (AT+4 °C) for 3 d. Both in-situ and ex-situ maximal electron transport rate (ETRmax ) and in situ gross photosynthesis (GP), measured by O2 evolution, presented highest values under HCHN, and lowest under HCLN, across all measuring systems. Maximal quantum yield ( F v /F m ), and ETRmax of photosystem (PS) II [ETR(II)max ] and PSI [ETR(I)max ], decreased under HCLN at AT+4 °C. Ex situ ETR was higher than in situ ETR. At noon, F v /F m decreased (indicating photoinhibition), whereas ETR(II)max and maximal non-photochemical quenching (NPQmax ) increased. ETR(II)max decreased under AT+ 4 °C in contrast to F v /F m, photosynthetic efficiency (α ETR ) and saturated irradiance (EK ). Thus, U. rigida exhibited a decrease in photosynthesis under acidification, changing LN, and AT+4 °C. These results emphasize the importance of studying the interaction between environmental parameters using in-situ versus ex-situ conditions, when aiming to evaluate the impact of global change on marine macroalgae.